Dad is fat - Gaffigan, Jim. (Crown Archetype, 2013)
"In Dad is Fat, stand-up comedian Jim Gaffigan, who's best known for his legendary riffs on Hot Pockets, bacon, manatees, and McDonald's, expresses all the joys and horrors of life with five young children--everything from cousins ("celebrities for little kids") to toddlers' communication skills ("they always sound like they have traveled by horseback for hours to deliver important news"), to the eating habits of four year olds ("there is no difference between a four year old eating a taco and throwing a taco on the floor"). Reminiscent of Bill Cosby's Fatherhood, Dad is Fat is sharply observed, explosively funny, and a cry for help from a man who has realized he and his wife are outnumbered in their own home"--